2014
DOI: 10.1016/j.cgh.2013.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Hydration With Lactated Ringer's Solution Reduces Pancreatitis After Endoscopic Retrograde Cholangiopancreatography

Abstract: Background & Aims Pancreatitis is the most common serious complication of endoscopic retrograde cholangiopancreatography (ERCP). We performed a pilot study to determine whether aggressive peri-procedural hydration with lactated Ringer’s solution reduces the incidence of pancreatitis following ERCP. Methods Patients who underwent first-time ERCP were randomly assigned to groups (2:1) that received aggressive hydration with lactated Ringer’s solution (3 cc/kg/hr during the procedure, a 20 cc/kg bolus after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(146 citation statements)
references
References 17 publications
5
133
0
8
Order By: Relevance
“…In adults the administration of plasma expanders is not recommended based on current evidence 60,69 . Aggressive intravenous hydration with lactated Ringer's solution appears to reduce the development of post-ERCP pancreatitis and is not associated with volume overload 72 . Other studies show no added benefit from lactated Ringer's solution compared to normal saline in terms of mortality and the duration of hospital stay 73 .…”
Section: (Grade 2/b Full Agreement)mentioning
confidence: 99%
See 1 more Smart Citation
“…In adults the administration of plasma expanders is not recommended based on current evidence 60,69 . Aggressive intravenous hydration with lactated Ringer's solution appears to reduce the development of post-ERCP pancreatitis and is not associated with volume overload 72 . Other studies show no added benefit from lactated Ringer's solution compared to normal saline in terms of mortality and the duration of hospital stay 73 .…”
Section: (Grade 2/b Full Agreement)mentioning
confidence: 99%
“…No specific pain management guidelines are available in pediatric AP. The World Health Organization recommendations for pain management in children should be considered [72]. In the presence of mild pain, paracetamol and ibuprofen are the medicines of choice.…”
Section: Ap-v2 Pain Managementmentioning
confidence: 99%
“…A pilot study on 62 average-risk patients showed that aggressive hydration was associated with a lower rate of post-ERCP pancreatitis (0% vs. 17%, p = 0.016) [29]. This interesting observation needs confirmation before it can be recommended in routine practice.…”
Section: Prevention Of Post-ercp Pancreatitismentioning
confidence: 97%
“…One important caveat is that additional skills are required to pass small guidewires deep into the pancreatic duct, so that the safety and value of the method are unproven in less experienced hands. Because of this and since more recent studies, as discussed earlier, have shown higher efficacy and cost-effectiveness as well as lower adverse events associated with rectal indomethacin as compared to pancreatic prophylactic stent placement or the combination of both methods, the use of prophylactic pancreatic stent placement may decrease [29,31].…”
Section: Pancreatic Stentingmentioning
confidence: 99%
“…Az ajánlást retrospektív [21] elemzés és egy kis esetszámú prospektív tanulmány [22] erősítette meg.…”
Section: Intravénás Folyadékbevitelunclassified